Role of topical Sucralfate in healing of burn wounds - Koshariya, Mahim; Shitole, Abhishek; Agarwal, Vibhore; Dave, S. (International Surgery Journal, 2018)
Background: Sucralfate is a basic aluminum salt of sucrose octasulphate which was orally taken for prevention and treatment of several gastrointestinal diseases. This study primarily aims to analyze whether sucralfate accelerates wound healing process in burn patients. The incidence of infection & relieve in pain in burn patients was also compared. Methods: This is an observational study carried out in the Department of General Surgery, Hamidia Hospital Bhopal on 50 patients divided into group 1 (sucralfate)and group 2 [a-sucralfate; b-silver sulfadiazine (SSD)]. Demographics, history, physical, and systemic examinations of the patients were recorded. Results: It was observed that sucralfate augments the formation of granulation tissue (in 6-17 days) as compared to SSD (14-22 days). It was noticed that faster healing by re-epithelialization was present in sucralfate group (11-22 days) as compared with SSD group (15-30 days). By the end of 3rd week 50-75% of wound was healed in sucralfate group as compared with 35-50% in SSD group. Incidence of secondary infection was less when topical sucralfate was used (group 1 = 25%; group 2a = 16.6%; group 2b = 66.66%). There was a marked relief in pain and discomfort after sucralfate application as compared to SSD. Conclusions: Using topical sucralfate expedite the burn wound healing process, significantly decreases pain with no local or systemic adverse reactions to the topical application therefore it can be used as an adjunctive or alternative agent in the future. However, multicentric trials with larger sample size are needed to insure the concept.